Association of cognitive reserve with 9-year domain-specific cognitive trajectories and risk of cognitive impairment in Mexican older adults - Martina Ferrari-Díaz; Ashuin Kammar-García; Juan Silva-Pereyra; Carmen García-Peña (PLoS ONE, 2025)
Cognitive reserve (CR) refers to the adaptation of cognitive performance to endure brain pathology or the aging process. CR can be categorized into static (education and occupation) or dynamic (leisure and physical activities) proxies. Typically, longitudinal studies assess CR as a composite score at baseline and cognitive performance as a global score. This study aimed to compare the relationship between different CR proxies (static and dynamic) with 9-year domain-specific cognitive trajectories, and the risk of cognitive impairment in older adults. Data from the latest four waves of the Mexican Health and Aging Study (MHAS; n = 3102, baseline mean age = 66.62 years) were used. Mixed effects models were performed with CR as independent variables and cognitive trajectories (verbal memory encoding and retrieval, verbal fluency, constructional praxis, visual attention, and memory) as outcomes. Education and leisure activities were significant positive predictors of all cognitive domains. Physical activities were a positive predictor of verbal fluency and verbal memory encoding only. Occupation was a positive predictor of verbal fluency and visual attention. Logistic regression analysis was performed to assess the relationship between CR and the risk of cognitive impairment, where education (OR: 0.79, 95% CI: 0.76, 0.83), occupational complexity (OR: 0.85, 95% CI: 0.77, 0.95), and leisure activities (OR: 0.96, 95% CI: 0.95, 0.97) were significant protective factors. Increasing the years of education can serve as a preventive strategy to delay the clinical manifestation of cognitive impairment while implementing leisure activities can act as an intervention to promote cognition even in later years.